The Assessment of State-Owned Bank Soundness Using RGEC Method Before and During Covid-19 Pandemic - Ilyas, Fransdito Ali; Setyorini, Christina Tri (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2023)
Covid-19 entered Indonesia in March of 2020, affecting nearly all sectors, including the finance industry. This study aims to analyze the financial performance of state-owned banks in Indonesia (BNI, BRI, Mandiri, and BTN) for the period 2018-2021 using the RGEC (risk profile, gcg, income, and capital) method. According to circular letter of Bank Indonesia (SE BI) no. 13 of 2011, each bank is required to conduct an independent assessment of its financial condition. This study employs a descriptive quantitative methodology. In this research, the purposive sampling method was used. The sample consists of state-owned institutions that have published annual reports from 2018 to 2021 consecutively. Documents and secondary data are the categories and sources of data utilized for this article. Based on the findings of this analysis as a whole, BNI bank has a very healthy predicate in 2018, 2019, and 2021, and a healthy predicate in 2020. BTN bank has a consecutively healthy predicate for the 2018-2021 period, while Mandiri bank and BRI bank have a consecutively very healthy predicate for the 2018-2021 period.